Comprehensive Study of Structural, Optical and EPR Properties of Mn2+ Doped CdSe Nanocrystals - Mani Tripathi Upendra; Kripal Ram; Vaish Garima (Journal of New Developments in Chemistry, 2023)
The synthesis of II-VI semiconductor nanocrystals doped with transition metal ions is particularly difficult. In the case of manganese doped CdSe nanocrystals produced via chemical route it is necessary to achieve small incorporation of manganese ions. The incorporation of manganese ions in CdSe nanocrystals has been confirmed by the study of Energy Dispersive Spectroscopy, Photoluminescence and Electron Paramagnetic Resonance spectra. The CdSe nanocrystals have cubic structure, the average crystallite size lies between 3-6 nm and increases with the variation of doping concentration of Mn2+ ions as characterized by X-ray diffraction. The structural properties of CdSe semiconductor nanocrystals are also studied by High Resolution Transmission Electron Microscopy, Scanning Electron Microscopy and UV- Visible Absorption Spectroscopy. The energy band gaps have been determined by UV/V is absorption study with the help of Tauc plot and are 2.54 eV, 2.27 eV and 2.24 eV as concentration of Mn2+ions in CdSe semiconductor nanocrystals increases from 0% to 0.75%. The crystallite size is also obtained from the UV-Visible absorption study; this varies from 1.69 to 1.78 nm with increase of Mn2+ concentration from 0% to 0.75% which is in agreement with X-ray diffraction result. Further, the magnetic and electronic properties of Mn2+ doped CdSe nanocrystals are studied using EPR spectra and the values of g factor, second-rank axial zero-field splitting parameter D and hyperfine parameter A are calculated. EPR measurements reveal that the dopant ions are incorporated in CdSe semiconductor nanocrystals.
Keywords: CdSe nanocrystals